Augmentation of anti-tumor immunity by adoptive T-cell transfer after allogeneic hematopoietic stem cell transplantation. Issue 4 (August 2012) - Bleakley, Marie; Turtle, Cameron J; Riddell, Stanley R
Allogeneic hematopoietic stem cell transplantation (HCT) is currently the standard of care for most patients with high-risk acute leukemias and some other hematologic malignancies. Although HCT can be curative, many patients who undergo allogeneic HCT will later relapse. There is, therefore, a critical need for the development of novel post-HCT therapies for patients who are at high risk for disease recurrence following HCT. One potentially efficacious approach is adoptive T-cell immunotherapy, which is currently undergoing a renaissance that has been inspired by scientific insight into the key issues that impeded its previous clinical application. Translation of the next generation of adoptive T-cell therapies to the allogeneic HCT setting, using donor T cells of defined specificity and function, presents a unique set of challenges and opportunities. The challenges, progress and future of adoptive T-cell therapy following allogeneic HCT are discussed in this review.